2018
DOI: 10.15252/embr.201846363
|View full text |Cite
|
Sign up to set email alerts
|

NDP 52 interacts with mitochondrial RNA poly(A) polymerase to promote mitophagy

Abstract: Parkin‐mediated mitophagy is a quality control pathway that selectively removes damaged mitochondria via the autophagic machinery. Autophagic receptors, which interact with ubiquitin and Atg8 family proteins, contribute to the recognition of damaged mitochondria by autophagosomes. NDP52, an autophagy receptor, is required for autophagic engulfment of damaged mitochondria during mitochondrial uncoupler treatment. The N‐terminal SKICH domain and C‐terminal zinc finger motif of NDP52 are both required for its fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 60 publications
1
20
1
Order By: Relevance
“…The described adaptor protein for the autophagic removal of inflammasomes, p62/SQSTM1 (Shi et al, 2012), did not colocalize with or bind to NLRP3. However, the murine protein still contains the SKICH and LIR domain and several domain-specific knock-out studies in CALCOCO2 showed that the SKICH domain is essential for binding TRIF, TRAF6 (Inomata et al, 2012), phosphorylated tau, amyloid-beta (Jo et al, 2014), and damaged mitochondria (Furuya et al, 2018). CALCOCO2 has been shown to be involved in mitophagy (Moore & Holzbaur, 2016) and xenophagy (Verlhac et al, 2015) in human cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The described adaptor protein for the autophagic removal of inflammasomes, p62/SQSTM1 (Shi et al, 2012), did not colocalize with or bind to NLRP3. However, the murine protein still contains the SKICH and LIR domain and several domain-specific knock-out studies in CALCOCO2 showed that the SKICH domain is essential for binding TRIF, TRAF6 (Inomata et al, 2012), phosphorylated tau, amyloid-beta (Jo et al, 2014), and damaged mitochondria (Furuya et al, 2018). CALCOCO2 has been shown to be involved in mitophagy (Moore & Holzbaur, 2016) and xenophagy (Verlhac et al, 2015) in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…Murine cells express only a truncated version of CALCOCO2 and its functionality is under discussion. However, the murine protein still contains the SKICH and LIR domain and several domain-specific knock-out studies in CALCOCO2 showed that the SKICH domain is essential for binding TRIF, TRAF6 (Inomata et al, 2012), phosphorylated tau, amyloid-beta (Jo et al, 2014), and damaged mitochondria (Furuya et al, 2018). The LIR domain specifically binds LC3C on the autophagosomal membrane, which then attracts all other ATG8 orthologues (von Muhlinen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…17 During mitophagy, NDP52 invades the mitochondrial inner membrane and interacts with mitochondrial RNA poly (A) polymerase (MTPAP) to regulate RNA stability. 50 Similarly, OPTN is recruited to autophagosomes during mitophagy. 8,19 Although OPTN accelerates autophagy of cancer cells, 37 we are unaware of studies into its role in mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…MTPAP has also been implicated in mitophagy, a process that involves the selective autophagic degradation of defective or damaged mitochondria (Furuya et al, 2018). The autophagy receptor NDP52 enters depolarized mitochondria and, together with MTPAP, forms an oligomeric autophagy receptor complex that presumably detects damaged mitochondria and facilitates their elimination.…”
Section: Noncanonical Polyadenylationmentioning
confidence: 99%
“…The autophagy receptor NDP52 enters depolarized mitochondria and, together with MTPAP, forms an oligomeric autophagy receptor complex that presumably detects damaged mitochondria and facilitates their elimination. The MTPAP‐NDP52 interaction itself and not the catalytic activity of MTPAP has been proposed to be important for mitophagy (Furuya et al, 2018).…”
Section: Noncanonical Polyadenylationmentioning
confidence: 99%